A prognostic model to calculate the probability of severe preeclampsia in healthy young reproductive age woman - Nataly I. Frolova; Tatiana E. Belokrinitskaya; Kristina A. Kolmakova (IP Berlin A.V., 2020)
Aim.To develop the prognostic model to calculate the probability of severe preeclampsia in healthy young reproductive age woman. Materials and methods.This study included two groups of healthy women aged 1835 years with spontaneous singleton pregnancy: 100 patients with severe preeclampsia (patient group), and 100 women with non-complicated pregnancy (control group). All women had not a risk factors of preeclampsia such as history of hypertension, autoimmune, metabolic, renal, or cardiac diseases, and family or individual history preeclampsia or thromboembolism before this pregnancy. Their body mass index in the 1-st trimester of gestation was 35 kg/sq. m. Gene polymorphisms were detected using the polymerase chain reaction-real time technique. The data were analyzed with methods of binary and multifactorial mathematical statistics. Our analysis of the predictive models was performed by using logistic regression. To determine the diagnostic value of the predictive models used the ROC-curve is followed by determining the area under it (AUC). Results.Some prognostic models to calculate the probability of severe preeclampsia were build using an anamnestic, clinical and genotypic characteristics and multifactorial analysis. Combination of genotypesAGTR2-1675АA/eNOS3-786СC; tobacco smoking; bacteriuria; acute respiratory infections and/or acute vulvovaginitis during 23 trimester of gestation were determinate as most informative predictors of severe preeclampsia. Logistic model included three predictors: bacteriuria; acute respiratory infections and/or acute vulvovaginitis during 23 trimester of gestation had higher prognostic value. ROC analysis identified a high specificity (89.58%) and sensitivity (76.47%) of the model, and the integral index of the effectiveness of predictive markers (AUC=0.885), according to the expert scale of values which is indicative of a very high quality model. Conclusion.It is recommended to use this elaborated predictive model for the purpose of individual risk assessment of severe preeclampsia in healthy young reproductive age woman.